Fish Traders' Attachment Patterns in Traditional Markets: A Case Study from Nanggalo District, Padang City, Indonesia - Lubis, Gebi Cahyani; Irwan, Irwan; Jannah, Latifah Izzatul; Amelia, Anggun (LPPM Universitas Jambi, 2025)
This study investigates the attachment patterns of fish traders in traditional markets, focusing on Nanggalo District, Padang City, Indonesia. The research employs a qualitative approach with a descriptive design. Purposive sampling was used to select research informants, who are fish traders with varying levels of attachment. Data collection methods included in-depth interviews, participant observation, and document analysis. The data analysis followed the model proposed by Miles and Huberman, consisting of data collection, data reduction, data display, and conclusion drawing. The findings reveal that the presence of fish traders in traditional markets is strongly influenced by collaborative relationships between traders during the fish procurement process. This collaboration is characterized by interactions between large agents, small agents, and traders, forming a network of trust. Over time, these interactions evolved from initial mutual acquaintance to a system of credit and installment-based transactions, allowing traders to take fish on credit. The attachment among traders is marked by this trust and a shift from initial exchange relationships to more flexible, long-term trading arrangements.